Composite diaphragm, preparation method thereof and secondary battery
By introducing vinylpyridine grafted butadiene styrene copolymer as a functional material in the battery separator, the problem of transition metal ions dissolution in high-voltage batteries is solved, and the circulation performance of the battery and the breathability of the separator are improved.
Patent Information
- Application Number
- CN202411497402.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-25
AI Technical Summary
In a high voltage battery system, the reaction of the positive electrode material with the electrolyte causes the transition metal ions to dissolve, destroying the SEI film on the surface of the negative electrode, causing the battery circulation performance to deteriorate. The breathability and uniformity of traditional diaphragms are insufficient, and the compatibility between the binder and complexing substances is poor.
A composite separator is used, which includes a base film and a functional layer consisting of a ceramic material and a vinylpyridine grafted butadiene styrene copolymer, which serves as a functional material to provide excellent bonding properties and transition metal ion adsorption properties. .
By improving the peel strength between the base film and the functional layer and the breathability of the composite separator, the damage of the SEI film by transition metal ions is reduced, and the circulation performance of the battery is significantly improved without the need for additional adhesives and complexing substances.
Smart Images

Figure BDA0005101623530000141 
Figure BDA0005101623530000151 
Figure BDA0005101623530000171
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a composite diaphragm and a preparation method thereof, and a secondary battery. Background Art
[0002] With the development and growth of the new energy industry chain, secondary batteries are widely used as energy storage devices in electric vehicles, communication equipment, portable electronic devices and other fields.
[0003] In pursuit of higher energy density of batteries, high-voltage positive electrode materials are currently mostly used, such as lithium manganese oxide, lithium nickel manganese oxide, lithium-rich manganese-based positive electrode materials, manganese-rich materials, etc. In high-voltage battery systems, positive electrode materials are easily reacted with electrolytes, causing the dissolution of transition metal ions such as manganese ions. The transition metal ions migrate to the negative electrode side and are reduced, and are deposited on the negative electrode surface, continuously destroying the SEI film on the negative electrode surface, causing the battery cycle performance to deteriorate.
[0004] In traditional technology, a complexing substance is usually set on the diaphragm to complex the transition metal ions dissolved in the positive electrode. However, the complexing substance needs to be used in combination with a binder. On the one hand, the coating thickness is large and the air permeability of the diaphragm is affected. On the other hand, the current complexing substance has poor compatibility with the binder, which affects the uniformity of the coating and the bonding strength with the diaphragm base membrane is also weak. Summary of the invention
[0005] Based on this, it is necessary to provide a composite diaphragm and a preparation method thereof, and a secondary battery to solve the above technical problems.
[0006] The first aspect of the present application provides a composite membrane, which includes: a base membrane; and a functional layer, which is arranged on the surface of at least one side of the base membrane, and the functional layer includes a ceramic material and a functional material, and the functional material includes a vinyl pyridine grafted butadiene styrene copolymer.
[0007] In some embodiments, based on the total mass of the vinylpyridine-grafted butadiene styrene copolymer, the mass proportion of butadiene is 20% to 69.5%, the mass proportion of styrene is 10% to 50%, and the mass proportion of vinylpyridine is 5% to 30%.
[0008] In some embodiments, the vinyl pyridine includes one or more of 2-vinyl pyridine, 3-vinyl pyridine, and 4-vinyl pyridine.
[0009] In some embodiments, the particle size of the functional material is 10 nm to 1000 nm.
[0010] In some embodiments, in the functional layer, the mass ratio of the functional material to the ceramic material is (1:99) to (10:90).
[0011] In some embodiments, the thickness of the functional layer is 1 μm to 5 μm.
[0012] In some embodiments, the peel strength between the functional layer and the base film is 0.01 kN / m to 0.05 kN / m.
[0013] In some embodiments, the composite membrane has an air permeability of 80 s / 100 ml to 500 s / 100 ml.
[0014] The second aspect of the present application provides a method for preparing the composite membrane provided in the first aspect, and the preparation method comprises the following steps: first dispersing the functional material in deionized water, and then adding the ceramic material for dispersion to form a functional layer slurry; wherein the functional material comprises vinyl pyridine grafted butadiene styrene copolymer; coating the functional layer slurry onto the base film, and forming a functional layer after drying to obtain a composite membrane.
[0015] A third aspect of the present application provides a secondary battery, which includes a positive electrode, a negative electrode, and the composite separator provided in the first aspect.
[0016] Compared with the traditional technology, this application has at least the following beneficial effects:
[0017] The composite membrane provided by the present application, through the excellent bonding performance and transition metal ion adsorption performance of vinyl pyridine grafted butadiene styrene copolymer, is used as a binder on the one hand to achieve good dispersibility and bonding between ceramic materials, improve the peeling strength between the base film and the functional layer, and on the other hand, it can adsorb transition metal ions, reduce the damage of transition metal ions to the SEI film, and improve the cycle performance of the battery. Therefore, vinyl pyridine grafted butadiene styrene copolymer is added to the functional layer of the composite membrane as a functional material, without the need to add additional binders and complexing substances, thereby improving the uniformity of the functional layer, reducing the thickness of the functional layer, and improving the air permeability of the composite membrane. DETAILED DESCRIPTION
[0018] References to embodiments of the present application will now be provided in detail, one or more examples of which are described below. Each example is provided as an explanation rather than a limitation of the present application. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present application without departing from the scope or spirit of the present application. For example, a feature described or described as part of one embodiment may be used in another embodiment to produce a further embodiment.
[0019] Therefore, it is intended that the present application covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present application are disclosed in or are apparent from the following detailed description. It will be appreciated by those of ordinary skill in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the present application.
[0020] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0021] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0022] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0023] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0024] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, it is mentioned that the method may also include step (c), which means that step (c) can be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0025] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0026] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0027] The first aspect of the present application provides a composite membrane, which includes a base membrane and a functional layer. The functional layer is arranged on the surface of at least one side of the base membrane, and the functional layer includes a ceramic material and a functional material, and the functional material includes a vinyl pyridine grafted butadiene styrene copolymer.
[0028] The composite membrane provided by the present application, through the excellent bonding performance and transition metal ion adsorption performance of vinyl pyridine grafted butadiene styrene copolymer, is used as a binder on the one hand to achieve good dispersibility and bonding between ceramic materials, improve the peeling strength between the base film and the functional layer, and on the other hand, it can adsorb transition metal ions, reduce the damage of transition metal ions to the SEI film, and improve the cycle performance of the battery. Therefore, vinyl pyridine grafted butadiene styrene copolymer is added to the functional layer of the composite membrane as a functional material, without the need to add additional binders and complexing substances, thereby improving the uniformity of the functional layer, reducing the thickness of the functional layer, and improving the air permeability of the composite membrane.
[0029] In some embodiments, based on the total mass of the vinylpyridine grafted butadiene styrene copolymer, the mass proportion of butadiene is 20% to 69.5%, the mass proportion of styrene is 10% to 50%, and the mass proportion of vinylpyridine is 5% to 30%. By regulating the mass proportion of butadiene, styrene and vinylpyridine in the vinylpyridine grafted butadiene styrene copolymer within a suitable range, the liquid absorption and retention capacity of the composite diaphragm can be effectively improved, so that the composite diaphragm has good bonding performance and transition metal ion adsorption performance at the same time, and the cycle performance of the battery is improved.
[0030] In some embodiments, the weight average molecular weight of the vinyl pyridine grafted butadiene styrene copolymer is 2000 to 200000. When the weight average molecular weight is within the above range, it is beneficial for the vinyl pyridine grafted butadiene styrene copolymer to ensure good adhesion and structural stability of the composite separator.
[0031] In some embodiments, the particle size of the functional material is 10nm to 1000nm, including but not limited to 10nm, 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, and 1000nm. Within the above particle size range, it is beneficial to improve the dispersibility of the functional material in deionized water and to form a uniform functional layer slurry. Further, the particle size of the vinyl pyridine grafted butadiene styrene copolymer is 100nm to 500nm.
[0032] In some embodiments, in the functional layer, the mass ratio of the functional material to the ceramic material is (1:99) to (10:90), including but not limited to 1:99, 2:98, 3:97, 4:96, 5:95, 6:94, 7:93, 8:92, 9:91, and 10:90. Within the above mass ratio range, the overall performance of the functional layer is optimized, taking into account the heat resistance, air permeability, mechanical stability, ion transmission performance, and transition metal ion adsorption performance of the functional layer. Further, the mass ratio of the functional material to the ceramic material is (3:97) to (8:92).
[0033] In some embodiments, the thickness of the functional layer is 1 μm to 5 μm, including but not limited to 1 μm, 2 μm, 3 μm, 4 μm, and 5 μm. Within the above thickness range, the composite diaphragm has good bonding properties and good transition metal ion adsorption properties while having high air permeability. Further, the thickness of the functional layer is 2 μm to 4 μm.
[0034] In some embodiments, the peel strength between the functional layer and the base film is 0.01 kN / m to 0.05 kN / m, including but not limited to 0.01 kN / m, 0.02 kN / m, 0.03 kN / m, 0.04 kN / m, and 0.05 kN / m. Within the above peel strength range, a strong bond between the functional layer and the base film is ensured, the risk of peeling of the functional layer during battery use is reduced, the mechanical stability of the separator is improved, the occurrence of short circuits is reduced, and the safety and cycle stability of the battery are improved. Furthermore, the peel strength between the functional layer and the base film is 0.3 kN / m to 0.5 kN / m.
[0035] In some embodiments, the vinyl pyridine includes one or more of 2-vinyl pyridine, 3-vinyl pyridine and 4-vinyl pyridine. Further, the vinyl pyridine is 2-vinyl pyridine.
[0036] In some embodiments, the ceramic material includes one or more of aluminum oxide, silicon oxide, titanium oxide, cerium oxide, calcium carbonate, calcium oxide, zinc oxide, magnesium oxide, cerium titanate, calcium titanate, barium titanate, lithium phosphate, lithium titanium phosphate, lithium aluminum titanium phosphate, lithium nitride, lithium lanthanum titanate, lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide, and lithium lanthanum zirconium tantalum oxide. The ceramic material is used to reduce the thermal shrinkage of the composite diaphragm and improve the safety of the composite diaphragm.
[0037] Furthermore, the ceramic material includes one or more of lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide, and lithium lanthanum zirconium tantalum oxide. In addition to improving the thermal stability of the ceramic material, these ceramic materials can also improve the ion transmission capacity of the composite diaphragm.
[0038] In some embodiments, the ceramic material is in a granular structure, and the particle size D of the ceramic material particles is V 50 is 0.3 μm to 1 μm, including but not limited to 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, and 1 μm. When the particle size of the ceramic particles is within this range, it is beneficial for the ceramic particles to be well dispersed in the functional layer and the uniformity of the functional layer to be improved.
[0039] In some embodiments, the base film includes a single-layer or multi-layer porous base film.
[0040] In some embodiments, the material of the base film is selected from one or more of polyolefin, aramid, polyimide, polyester fiber, acrylic fiber, and polyvinylidene fluoride.
[0041] In some embodiments, the base film has a thickness of 5 μm to 20 μm, including but not limited to 5 μm, 10 μm, 15 μm, and 20 μm.
[0042] In some embodiments, the air permeability of the composite membrane is 80s / 100ml to 500s / 100ml, including but not limited to 80s / 100ml, 100s / 100ml, 150s / 100ml, 200s / 100ml, 250s / 100ml, 300s / 100ml, 350s / 100ml, 400s / 100ml, 450s / 100ml, and 500s / 100ml. Within the above air permeability range, the composite membrane has good air permeability, which is conducive to the penetration of the electrolyte, improves the ion conductivity of the battery, reduces the internal resistance of the battery, and thus improves the cycle performance and service life of the battery. Further, the air permeability of the composite membrane is 100s / 100ml to 300s / 100ml.
[0043] The second aspect of the present application provides a method for preparing the composite diaphragm provided in the first aspect, the preparation method comprising the following steps:
[0044] S1. Firstly, the functional material is dispersed in deionized water, and then the ceramic material is added and dispersed to form a functional layer slurry.
[0045] Among them, the functional material includes vinyl pyridine grafted butadiene styrene copolymer.
[0046] S2. The functional layer slurry is coated on the base film, and after drying, a functional layer is formed to obtain a composite diaphragm.
[0047] The preparation method of the composite diaphragm of the present application disperses the functional material first and then adds the ceramic material for dispersion, thereby reducing the agglomeration of the ceramic material and making the ceramic material evenly dispersed in the vinyl pyridine grafted butadiene styrene copolymer of the functional material, thereby improving the uniformity of the functional layer.
[0048] A third aspect of the present application provides a secondary battery, which includes a positive electrode, a negative electrode, and the composite separator provided in the first aspect.
[0049] In some embodiments, the positive electrode includes a positive electrode active material, and the positive electrode active material includes at least one transition metal element.
[0050] In some embodiments, the transition metal element is one of nickel, cobalt and manganese.
[0051] positive electrode:
[0052] In some embodiments of the present invention, the secondary battery provided by the present invention includes a positive electrode, the positive electrode includes a positive electrode current collector and a positive electrode material layer disposed on the positive electrode current collector, and the positive electrode material layer includes a positive electrode active material. The positive electrode active material includes a compound that reversibly embeds and deintercalates lithium ions. In the present invention, the positive electrode active material includes at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium-rich manganese-based positive electrode material, and lithium nickel cobalt manganese oxide. They can be used alone or in any combination of two or more.
[0053] In some embodiments of the present invention, the positive electrode material layer further includes a binder, which improves the bonding between the positive electrode active material particles and also improves the bonding between the positive electrode material layer and the positive electrode current collector.
[0054] In some embodiments of the present invention, non-limiting examples of binders include polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, and the like.
[0055] In some embodiments of the present invention, the cathode material layer includes a conductive agent to impart conductivity to the electrode. The conductive agent may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.
[0056] In some embodiments of the present invention, the positive electrode sheet includes a positive electrode current collector. Exemplarily, the positive electrode current collector may be aluminum (Al), but is not limited thereto.
[0057] In some embodiments of the present invention, the positive electrode plate provided by the present invention further includes a second solid electrolyte powder for improving the ionic conductivity of the composite positive electrode. The present invention does not limit the type of the second solid electrolyte powder, which may be an oxide solid electrolyte powder, a sulfide solid electrolyte powder, or a halide solid electrolyte powder. Optionally, the mass of the second solid electrolyte powder accounts for 1%-20% of the mass of the positive electrode plate; preferably 5%-20%.
[0058] In some embodiments of the present invention, the thickness of the positive electrode material layer in the positive electrode plate provided by the present invention is 30-400 μm, for example, 30 μm, 40 μm, 50 μm, 80 μm, 110 μm, 200 μm, 300 μm, 400 μm, preferably 50-110 μm.
[0059] Negative electrode:
[0060] In some embodiments of the present invention, the negative electrode sheet includes a current collector and a negative electrode active material layer disposed on the current collector.
[0061] In the present invention, the specific types of negative electrode active materials are not subject to specific restrictions and can be selected according to needs. Specifically, the negative electrode active material is selected from natural graphite, artificial graphite, mesophase microcarbon beads (MCMB for short), hard carbon, soft carbon, silicon, silicon-carbon composites, Li-Sn alloys, Li-Sn-O alloys, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 , Li-Al alloy. Non-limiting examples of carbon materials include crystalline carbon, amorphous carbon and mixtures thereof. Crystalline carbon can be amorphous or flake-shaped, platelet-shaped, spherical or fibrous natural graphite or artificial graphite. Amorphous carbon can be soft carbon, hard carbon, mesophase pitch carbide, calcined coke, etc.
[0062] In some embodiments of the present invention, metal elements and metal compounds can also be selected as negative electrode active materials, such as compounds containing metals or metalloids such as Li, Ag, Al, Bi, Cu, Ga, Ge, In, Ni, Pb, Sb, Si, Sn, Sr, and Zn.
[0063] In some embodiments of the present invention, the mass percentage of the negative electrode active material contained in the negative electrode active material layer can be 80%-99%, for example, 80%, 85%, 90%, 95%, 97%, 99%, etc., preferably 95%-97%.
[0064] In some embodiments of the present invention, the negative electrode material layer may include a binder; the binder improves the bonding between negative electrode active material particles and the bonding between the negative electrode active material and the current collector.
[0065] In some embodiments of the present invention, non-limiting examples of binders include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, and the like.
[0066] In some embodiments of the present invention, the negative electrode active material layer can be obtained by coating a negative electrode slurry on a negative electrode current collector and then drying the negative electrode slurry, wherein the negative electrode slurry includes at least a negative electrode active material and a negative electrode binder. When an aqueous solvent is used as a liquid medium for forming the negative electrode slurry, a thickener is preferably used for slurrying, and the thickener can generally be used to adjust the viscosity of the slurry.
[0067] In some embodiments of the present invention, the aforementioned thickener may be one or more of the following: carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein and salts thereof.
[0068] In some embodiments of the present invention, the mass proportion of the thickener in the negative electrode slurry can be 0.1%-5%, for example, 0.1%, 0.2%, 0.5%, 0.6%, 1%, 2%, 3%, 4%, 5%, etc., preferably 0.5%-3%, and more preferably 0.6%-2%.
[0069] In some embodiments of the present invention, the negative electrode active material layer includes a conductive material, so that the electrode has conductivity. The conductive material may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., such as copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.
[0070] In some embodiments of the present invention, the negative electrode current collector may be selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.
[0071] Electrolyte:
[0072] The lithium battery and electrochemical device of the present invention also include an electrolyte.
[0073] In some embodiments of the present invention, the electrolyte includes a lithium salt and a solvent.
[0074] In some embodiments of the present invention, the lithium salt includes at least one of an organic lithium salt or an inorganic lithium salt. In some embodiments of the present invention, the lithium salt includes, but is not limited to: lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), bistrifluoromethanesulfonyl imide lithium LiN(CF3SO2)2 (LiTFSI), bis(fluorosulfonyl)imide lithium Li(N(SO2F)2) (LiFSI), lithium bis(oxalate borate) LiB(C2O4)2 (LiBOB) or lithium di(oxalate borate) LiBF2(C2O4) (LiDFOB).
[0075] In some embodiments of the present invention, the solvent can be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0076] In some embodiments of the present invention, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, additives that improve battery low temperature performance, etc.
[0077] In some embodiments of the present invention, the aforementioned additives include at least one of 1,3-propane sultone, 1,4-butane sultone, propenyl-1,3-sultone, vinyl sulfate, 4-methyl vinyl sulfate, propenyl sulfate, saturated phosphate compounds and unsaturated phosphate compounds, tris(trimethylsilane) phosphate, tris(trimethylsilane) borate, tris(triethylsilane) borate, succinonitrile, glutaronitrile, ethylene glycol bis(propionitrile) ether, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid nitrile, and sebaconitrile.
[0078] Secondary battery:
[0079] In some embodiments of the present invention, the secondary battery of the present invention comprises the above-mentioned positive electrode sheet, negative electrode sheet, separator, electrolyte, etc., but is not limited thereto.
[0080] In some embodiments of the present invention, the secondary battery of the present invention is made by stacking the above-mentioned positive and negative electrode sheets.
[0081] In some embodiments of the present invention, the secondary battery of the present invention may include an outer package, which may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.
[0082] In some embodiments of the present invention, the present invention further provides a battery module. The battery module includes the above-mentioned secondary battery. The number of secondary batteries contained in the battery module of the present invention can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.
[0083] In some embodiments of the present invention, the present invention further provides a battery pack, which includes the above-mentioned battery module. The number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0084] Device:
[0085] The present invention also provides a device, which includes at least one of the above-mentioned secondary battery, battery module or battery pack.
[0086] In some embodiments of the present invention, the device includes, but is not limited to: electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, power storage systems, etc. In order to meet the device's requirements for high power and high energy density of lithium batteries, a battery pack or battery module can be used.
[0087] In other embodiments of the present invention, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a lithium battery may be used as a power source.
[0088] The present invention will be further described below in conjunction with the examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention.
[0089] The present invention is further described below by way of specific examples. The various chemical reagents used in the examples of the present invention are obtained through conventional commercial channels unless otherwise specified. Unless otherwise specified, the contents described below are all weight contents. Unless otherwise specified, it is understood that the process is carried out at room temperature.
[0090] The present application will be further described below with reference to specific embodiments and comparative examples.
[0091] Examples 1 to 11
[0092] Preparation of functional materials:
[0093] Step 1, preparation of aqueous pre-emulsion: prepare aqueous pre-emulsion with deionized water, rosin soap solution, fatty acid soap solution, sodium dodecylbenzene sulfonate, alkylphenol polyoxyethylene ether, sodium methylene dinaphthalene sulfonate and potassium chloride.
[0094] Step 2, preparation of oil phase solution: prepare an oil phase solution with tert-dodecyl mercaptan, 2-vinylpyridine, styrene and butadiene for use.
[0095] Step 3, latex synthesis: put the aqueous pre-emulsion and the oil phase solution into a reactor, add initiator azobisisoheptanenitrile to promote the reaction, and after reacting for 15 to 20 hours, the functional material vinyl pyridine grafted butadiene styrene copolymer can be obtained.
[0096] Preparation of composite diaphragm:
[0097] S1. Firstly, the functional material vinyl pyridine grafted butadiene styrene copolymer is dispersed in deionized water, and then the ceramic material alumina is added and dispersed to form a functional layer slurry.
[0098] Among them, the ceramic material is granular, with a particle size of D v 50 is 0.5μm.
[0099] S2. The functional layer slurry is coated on the base film, and after drying, a functional layer is formed to obtain a composite diaphragm.
[0100] The base film is a single-layer polyethylene porous base film, and the thickness of the base film is 29 μm.
[0101] Preparation of secondary batteries:
[0102] The positive electrode, the composite separator, the negative electrode stack, the primary packaging, the liquid injection (EC:DMC=1:1 vol%) and the secondary packaging are used to prepare the secondary battery.
[0103] The positive electrode includes a positive electrode active material, and the positive electrode active material includes lithium manganate; the negative electrode includes a negative electrode active material, and the negative electrode active material includes graphite.
[0104] In the examples prepared according to the above method, specific parameters are shown in Table 1 below.
[0105] Table 1
[0106]
[0107]
[0108] Comparative Example 1
[0109] Preparation of composite diaphragm:
[0110] S1. Firstly, the functional material poly (4-vinylpyridine) and the binder PVDF are dispersed in N-methylpyrrolidone, and then the ceramic material alumina is added and dispersed to form a functional layer slurry.
[0111] Among them, the ceramic material is granular, with a particle size of D v 50 is 0.5 μm; the mass ratio of poly(4-vinylpyridine), PVDF and ceramic material is 3:2:95.
[0112] S2. The functional layer slurry is coated on the base film, and after drying, a functional layer is formed to obtain a composite diaphragm.
[0113] The base film is a single-layer polyethylene porous base film, and the thickness of the base film is 29 μm; the thickness of the functional layer is 2 μm.
[0114] Preparation of secondary batteries:
[0115] The positive electrode, the composite separator, the negative electrode stack, the primary packaging, the liquid injection (EC:DMC=1:1 vol%) and the secondary packaging are used to prepare the secondary battery.
[0116] The positive electrode includes a positive electrode active material, and the positive electrode active material includes lithium manganate; the negative electrode includes a negative electrode active material, and the negative electrode active material includes graphite.
[0117] Comparative Example 2
[0118] Preparation of composite diaphragm:
[0119] S1. Add ceramic material alumina and binder CMC into deionized water for dispersion to form a functional layer slurry.
[0120] Among them, the ceramic material is granular, with a particle size of D v 50 is 0.5μm.
[0121] S2. The functional layer slurry is coated on the base film, and after drying, a functional layer is formed to obtain a composite diaphragm.
[0122] The base film is a single-layer polyethylene porous base film, and the thickness of the base film is 29 μm; the thickness of the functional layer is 2 μm.
[0123] Preparation of secondary batteries:
[0124] The positive electrode, the composite separator, the negative electrode stack, the primary packaging, the liquid injection (EC:DMC=1:1 vol%) and the secondary packaging are used to prepare the secondary battery.
[0125] The positive electrode includes a positive electrode active material, and the positive electrode active material includes lithium manganate; the negative electrode includes a negative electrode active material, and the negative electrode active material includes graphite.
[0126] Comparative Example 3
[0127] Preparation of composite diaphragm:
[0128] S1. Firstly, the functional material styrene-butadiene is dispersed in deionized water, and then the ceramic material alumina is added and dispersed to form a functional layer slurry.
[0129] Among them, the ceramic material is granular, with a particle size of D v 50 is 0.5 μm; the mass ratio of styrene-butadiene to ceramic material is 5:95.
[0130] S2. The functional layer slurry is coated on the base film, and after drying, a functional layer is formed to obtain a composite diaphragm.
[0131] The base film is a single-layer polyethylene porous base film, and the thickness of the base film is 29 μm; the thickness of the functional layer is 2 μm.
[0132] Preparation of secondary batteries:
[0133] The positive electrode, the composite separator, the negative electrode stack, the primary packaging, the liquid injection (EC:DMC=1:1 vol%) and the secondary packaging are used to prepare the secondary battery.
[0134] The positive electrode includes a positive electrode active material, and the positive electrode active material includes lithium manganate; the negative electrode includes a negative electrode active material, and the negative electrode active material includes graphite.
[0135] Performance Testing
[0136] (1) Peel strength test
[0137] Take a square separator with a width of 20 mm, stretch the sample and the tape at a speed of 2 mm / min, and determine the peel strength of the separator based on the peel force.
[0138] (2) Air permeability test
[0139] Place a 50mm×50mm membrane in an air permeability tester and record the time required for 100ml of air to pass through, which is the air permeability value.
[0140] (3) Thermal shrinkage test
[0141] First, the diaphragm is cut into discs with a diameter of 20 mm using a punching machine, and its initial area S0 is calculated. Then, the oven temperature is raised to the test temperature of 130°C, and the diaphragm disc sample is placed in the oven for 1 hour and then taken out. The diameter of the diaphragm after heat treatment is measured, and the corresponding area S1 is calculated. The heat shrinkage rate is calculated using the following formula:
[0142]
[0143] (4) Liquid absorption and retention test
[0144] Cut a 50mm×50mm sample and weigh it to get the initial weight. Immerse the sample completely in a beaker containing a certain amount of electrolyte, seal the beaker with plastic wrap, take out the test strip with tweezers after 1 hour, wipe the electrolyte on the surface with filter paper, weigh and record the weight of the membrane after absorbing the liquid; place the test strip in a clean beaker and continue to place it in a fume hood for 1 hour, weigh and record the weight of the membrane after it is left to stand. Calculate the liquid absorption rate of the membrane by the following formula (1), and calculate the liquid retention rate of the membrane by the following formula (2):
[0145]
[0146] (5) Transition metal ion test on the negative electrode side
[0147] Weigh two portions of about 0.1g of negative electrode powder (accurate to ±0.0003g) of each embodiment and comparative example, place in a 100mL beaker, add a small amount of distilled water to wet the bottom of the cup, then add 5mL, 12mol / L aqua regia to dissolve, heat on an electric heating plate for 20min, remove and cool, dilute and test. The prepared series of standard solutions are introduced into the iCAP7000 inductively coupled plasma spectrometer (ICP) instrument, and the intensity of each element in the standard solution is measured at the wavelength of the element to be measured (lithium, nickel, cobalt and manganese). When the linear correlation coefficient of the working curve is r≥0.9995, the measurement can be performed. The test results are shown in Table 2.
[0148] (6) Battery cycle performance test
[0149] The secondary batteries in each embodiment and comparative example were respectively taken and cycled for 800 cycles at room temperature using 1C / 1C charge and discharge conditions with a voltage range of 3.0V to 4.5V, and the average value of the ratio of the discharge capacity of the battery in the 800th cycle to the discharge capacity in the first cycle was calculated. The test results are shown in Table 2.
[0150] Table 2
[0151]
[0152]
[0153] As shown in Table 2, by comparing Examples 1 to 11 and Comparative Examples 1 to 3, it can be seen that the diaphragm and secondary battery provided in the present application improve the peel strength between the base film and the functional layer, can adsorb transition metal ions, reduce the damage of transition metal ions to the SEI film, improve the cycle performance of the battery, and improve the air permeability of the composite diaphragm.
[0154] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the technical concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
Claims
1. A composite diaphragm, characterized in that: include: Basement membrane; as well as The functional layer is arranged on the surface of at least one side of the base film, and the functional layer comprises a ceramic material and a functional material, and the functional material comprises a vinyl pyridine grafted butadiene styrene copolymer.
2. The composite diaphragm according to claim 1, characterized in that: Based on the total mass of the vinylpyridine-grafted butadiene styrene copolymer, the mass proportion of butadiene is 20% to 69.5%, the mass proportion of styrene is 10% to 50%, and the mass proportion of vinylpyridine is 5% to 30%.
3. The composite diaphragm according to claim 1, characterized in that: The vinyl pyridine includes one or more of 2-vinyl pyridine, 3-vinyl pyridine and 4-vinyl pyridine.
4. The composite diaphragm according to claim 1, characterized in that: The particle size of the functional material is 10nm to 1000nm.
5. The composite diaphragm according to claim 1, characterized in that: In the functional layer, the mass ratio of the functional material to the ceramic material is (1:99) to (10:90).
6. The composite diaphragm according to claim 1, characterized in that: The peeling strength between the functional layer and the base film is 0.01 kN / m to 0.05 kN / m.
7. The composite diaphragm according to claim 1, characterized in that: The thickness of the functional layer is 1 μm to 5 μm.
8. The composite diaphragm according to any one of claims 1 to 6, characterized in that: The air permeability of the composite membrane is 80s / 100ml to 500s / 100ml.
9. A method for preparing a composite diaphragm according to any one of claims 1 to 8, characterized in that: The following steps are involved: Firstly, the functional material is dispersed in deionized water, and then the ceramic material is added and dispersed to form a functional layer slurry; Wherein, the functional material comprises vinyl pyridine grafted butadiene styrene copolymer; The functional layer slurry is coated on the base film, and after drying, a functional layer is formed to obtain a composite diaphragm.
10. A secondary battery, characterized in that: The invention comprises a positive electrode, a negative electrode and the composite separator according to any one of claims 1 to 8.
Citation Information
Patent Citations
Thermal closed pore diaphragm as well as preparation method and application thereof
CN114039168A
Separator for lead storage battery, and lead storage battery
CN116018719A